Legal Policy of Water Resources Management by Local Governments: A Review of Right to Water in Indonesia - Astriani, Nadia (Hasanuddin Law Review, 2016)
This study is based by the cancellation of Act No. 7 of 2004 on Water Resources by the Indonesian Constitutional Court. Over the past 10 years, the law is the basis for the water resources management in Indonesia. The cancellation of the law would provide great impact for water resources management policy, especially with regard to the provision of right to water. Hence, this study aimed to determine the legal status of Right to Water provided by the local government after the cancellation of Act No. 7 of 2014 on Water Resources. The object of this normative study includes legal principles and systematic. This is due to the focus of this study is the meaning of the right principle to ruled state in the context of realizing the peoples’ prosperity and the position of Water Resources Act as the basis for the issuance of Government Regulation and Right to Water. The results of study indicate that in order to provide legal certainty for permit holder for Right to Use Water and Right to Commercialize Water, the ministry has issued various ministerial regulations, although the nature of these regulations only fills a legal vacuum. In the case of permit to Use of Water Resources, all permits for use of water resources that use surface water issued before the decision of Constitutional Court No. 85/PUU-XI/2013 are still valid. To permit referred to it, evaluation is conducted based on 6 (six) the principles of water resources management. Request new permit are in the process or for renewal of permit to use water resources that use surface water, processed as 6 (six) principles of water resources management. Although, in order to ensure legal certainty, the government should immediately issues the Act in Lieu of Water Resources Management which will be the basis for water resources management in Indonesia.